Jesus or Christ?: essays by G. Tyrrell ... [et al.] - Tyrrell, George (The Hibbert journal / Supplement, 1909)
Contents: The point at issue / by G. Tyrrell -- "Who say ye that I am?" / by E.S. Talbot -- Jesus, our Saviour / H. Weinel -- Jesus or Christ? : a pragmatist view / Percy Gardner -- The Christ of theology and the Jesus of history / by Paul Wilh. Schmiedel -- The idealism of Jesus / by Henry Jones -- The rationality of the Incarnation / by Richard Morris -- A divine Incarnation / by Sir Oliver Lodge -- The Jesus of history and the Christ of religion / by Henry Scott Holland -- One Lord Jesus Christ / by Joseph Rickaby -- Father, Son, and Holy Spirit--their relationships in modern thought / by Nathan Söderblom -- Faith and fact / by A.E. Garvie -- Jesus or Christ? / R.J. Campbell -- Jesus Christ and his teaching